In Situ Wood Fiber Dyeing Through Laccase Catalysis for Fiberboard Production - Colella, Alberto; De Chiaro, Addolorata; Lettera, Vincenzo (Frontiers in Bioengineering and Biotechnology, 2021)
Aim of the present work was to develop an innovative and environmentally friendly process for wood fibers dyeing, able to produce fully and 3-dimensionally colored Medium Density Fiberboard (MDF). The potential of laccase-catalyzed polymerization of precursors to form dyes useful in fiberboard manufacturing, a technique used for the first time in this field, was demonstrated. Several of the 7 tested aromatic compounds yielded colored products after laccase treatment in both acid and alkaline conditions and a good variety of colors was attained by using mixtures of two different monomers. To demonstrate the coloration and design potential of laccase conversion of aromatic compounds, MDFs were enzymatically dyed using in situ one step laccase-catalyzed coloration process and results were compared against commercial products obtained by using organic coloring agents. Important advantages over conventional processing methods include good color fastness, and, in some cases, new hydrophobic proprieties, allowing designers and woodworkers to explore the beauty of textures and the use of simpler and milder processing conditions that eliminate harsh chemical use and reduce energy consumption.